1262. Antimicrobial Activity of Gepotidacin against Clinical Isolates of Escherichia coli and Staphylococcus saprophyticus Collected Worldwide in 2019. (31st December 2020) - Arends, S J Ryan; Butler, Deborah; Scangarella-Oman, Nicole; Castanheira, Mariana; Mendes, Rodrigo E
Abstract: Background: Gepotidacin (GSK2140944) is a novel triazaacenaphthylene bacterial type II topoisomerase inhibitor in Phase 3 clinical development for the treatment of gonorrhea and uncomplicated urinary tract infections (UTI). This study reports on interim results from a global surveillance program to monitor the in vitro activity of gepotidacin and comparator agents when tested against contemporary Escherichia coli (EC) and Staphylococcus saprophyticus (SSAP) clinical isolates collected from patients with UTIs worldwide as part of the SENTRY Antimicrobial Surveillance Program. Methods: A total of 1, 467 EC and 92 SSAP isolates were collected from 73 medical centers located in US (38), Europe (27), Asia-Pacific region (4), and Latin America (4). These isolates were tested for susceptibility by reference methods in a central laboratory (JMI Laboratories). MIC results for gepotidacin and comparators were interpreted as per US FDA and EUCAST criteria. Isolates were from UTIs, 70% of which were from ambulatory, outpatient, emergency, and family practice medical services. Results: Gepotidacin (MIC50/90, 2/4 mg/L) displayed activity against 1, 467 EC isolates with 98.2% of all observed MICs ≤ 4 mg/L. Susceptibility rates of trimethoprim-sulfamethoxazole (TMP-SMX; MIC50/90, ≤ .12/ > 16 mg/L), ciprofloxacin (MIC50/90, 0.015/ > 4 mg/L), and amoxicillin-clavulanate (MIC50/90, 8/16 mg/L) were 67.1%, 72.9%, and 78.7% (CLSI), respectively. Greater susceptibility against EC isolates was seen for fosfomycin (MIC50/90, 0.5/1 mg/L; 99.0%S), nitrofurantoin (MIC50/90, 16/32 mg/L; 97.4%S), and meropenem (≤ 0.015/0.03 mg/L; 100%S). An ESBL phenotype was observed in 15.3% of EC isolates; gepotidacin (MIC50/90, 2/4 mg/L) remained active against these isolates. Gepotidacin (MIC50/90, 0.06/0.12 mg/L) also was active against 92 SSAP isolates, with 100% of MICs ≤ 0.25 mg/L. Susceptibility of SSAP isolates to TMP-SMX, ciprofloxacin, or nitrofurantoin was greater than 98.8% (CLSI), while fosfomycin showed little activity (MIC50/90, 64/ > 256 mg/L; 98.9% R [EUCAST]). Conclusion: Gepotidacin demonstrated potent activity against contemporary Escherichia coli, including ESBL-producing isolates and S. saprophyticus isolates collected worldwide. Table 1 Disclosures: S. J. Ryan Arends, PhD, Allergan (Research Grant or Support)Cipla Ltd. (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support) Deborah Butler, n/a, GlaxoSmithKline (Employee) Nicole Scangarella-Oman, MS, GlaxoSmithKline plc. (Employee, Shareholder) Mariana Castanheira, PhD, 1928 Diagnostics (Research Grant or Support)A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Amplyx Pharmaceuticals (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Fox Chase Chemical Diversity Center (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Paratek Pharma, LLC (Research Grant or Support)Pfizer (Research Grant or Support)Qpex Biopharma (Research Grant or Support) Rodrigo E. Mendes, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Basilea Pharmaceutica International, Ltd (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support)